Temperature and pH dual-responsive behavior of polyhedral oligomeric silsesquioxane-based star-block copolymer with poly(acrylic acid-block-N-isopropylacrylamide) as arms - Bai, Yu (2013)
Poly(acrylic acid-block-N-isopropylacrylamide) (PAAc-b-PNIPAm)-tethered octafunctional polyhedral oligomeric silsesquioxane (POSS) were synthesized via POSSinitialized atom transfer radical polymerization. When very short PAAc blocks are placed between the POSS core and PNIPAm short chains, the critical temperature (Tc) of POSSPAAc- b-PNIPAm determined by cloud point measurements varies in a wide temperature range with pH, and its Tc is even lower than that of POSS-PNIPAm with similar chain length at pH05.0, indicating a synergic effect between high local chain density and intramolecular interaction between PAAc and PNIPAm. When the PAAc blocks are relatively long, the pH response of POSS-PAAc-b- PNIPAm diminishes owing to the reduced local PNIPAm chain density.